Researchers' Self-Efficacy as a Determinant of Their Commitment to Duties in Universities in Anambra State, Nigeria - Akujieze M.O. (Budapest International Research and Critics University, 2023)
This study explores the relationship between researchers' self-efficacy and their commitment to duties in universities in Anambra State, Nigeria. The research aims to investigate the extent to which self-efficacy influences researchers' commitment levels and identify the implications for academic institutions. A descriptive survey design was employed, and data were collected through a questionnaire administered to lecturers in federal and state universities in Anambra State. The sample size consisted of 200 lecturers selected via simple random sampling. The questionnaire items were designed to measure self-efficacy and commitment to duties using a Likert scale. The data were analyzed using bivariate correlational analyses, specifically Pearson product moment correlations. The study revealed a negative linear relationship between researchers' self-efficacy and their commitment to duties, indicating that lower self-efficacy levels corresponded to diminished commitment. These findings highlight the importance of supporting researchers' self-efficacy through training, mentorship, and resource provision. Recommendations include enhancing self-efficacy development programs, fostering a positive research culture, providing adequate resources and support, implementing mentoring initiatives, and promoting research collaborations. By implementing these recommendations, universities in Anambra State can foster a culture of commitment and excellence among researchers, thereby enhancing productivity and contributing to the advancement of knowledge in the academic community.